CONDUCTING QUALITATIVE RESEARCH INTERVIEWS WITH PALLIATIVE AND END OF LIFE CARE PATIENTS IN THE HOME SETTING; REFLECTIONS AND RECOMMENDATIONS FROM AN ACADEMIC PALLIATIVE CARE RESEARCH CENTRE. Issue 1 (1st March 2015) - Sivell, S; Prout, H; Baillie, J; Byrne, A; Edwards, M; Harrop, E; Hopewell-Kelly, N; Noble, S; Sampson, C; Nelson, A
Abstract : Introduction: Within palliative and end-of-life research, qualitative research interviews are often undertaken in the home. Despite practical and ethical challenges, little attention has been given in the literature to the impact of the home setting on both participants and researchers. Aim(s) and method(s): We present the views and experiences of researchers from an academic palliative care research centre on conducting qualitative research with vulnerable populations in the home. Our researchers come from a range of backgrounds (including nursing, occupational therapy, social science, psychology and palliative medicine) with varying degrees of experience. Results: We reflect on several important ethical and practical issues, including ways in which to build rapport in often singular encounters and applying sensitivity and flexibility in difficult circumstances. The research interview has the potential to become therapeutic for the participant. However, interviewers need to be aware of unintentional power relationships between the researcher and the patient, and the implications for data quality, as well as both patients' and interviewers' physical and emotional well-being. Conclusion(s): In this setting, and with this particular patient group, less attention should be paid to interviewers' professional stance of neutrality and non-disclosure and more to allowing appropriate social contact, and humanity. However, care needs to be taken to avoid creating a false rapport and therapeutic environment. We offer a list of recommendations to address both practical and ethical concerns for researchers working in this field.